The Circuitry of Olfactory Projection Neurons in the Brain of the Honeybee, Apis mellifera - Zwaka, Hanna; Münch, Daniel; Manz, Gisela; Menzel, Randolf; Rybak, Jürgen (Frontiers in Neuroanatomy, 2016)
In the honeybee brain, two prominent tracts – the medial and the lateral antennal lobe tract – project from the primary olfactory center, the antennal lobes (ALs), to the central brain, the mushroom bodies (MBs), and the protocerebral lobe (PL). Intracellularly stained uniglomerular projection neurons were reconstructed, registered to the 3D honeybee standard brain atlas, and then used to derive the spatial properties and quantitative morphology of the neurons of both tracts. We evaluated putative synaptic contacts of projection neurons (PNs) using confocal microscopy. Analysis of the patterns of axon terminals revealed a domain-like innervation within the MB lip neuropil. PNs of the lateral tract arborized more sparsely within the lips and exhibited fewer synaptic boutons, while medial tract neurons occupied broader regions in the MB calyces and the PL. Our data show that uPNs from the medial and lateral tract innervate both the core and the cortex of the ipsilateral MB lip but differ in their innervation patterns in these regions. In the mushroombody neuropil collar we found evidence for ALT boutons suggesting the collar as a multi modal input site including olfactory input similar to lip and basal ring. In addition, our data support the conclusion drawn in previous studies that reciprocal synapses exist between PNs, octopaminergic-, and GABAergic cells in the MB calyces. For the first time, we found evidence for connections between both tracts within the AL.